Fath al-Dzari'ah Solution for Determining the Status of Children from Secret Marriages Through the Constitutional Court Decision - Nurjanah, Siti; Hermanto, Agus; Arif, M. Yasin al (JURNAL LEGALITAS, 2024)
Marriage in secret (nikah sirri), also known as clandestine marriage or unofficial marriage, will have implications on the status of the marriage, which is not considered valid according to the State. Meanwhile, an invalid marriage will also impact the illegitimacy of the child's status. In reality, the Constitutional Court changed this rule with a statement that the child still has biological lineage to the person who caused their birth, as long as it can be proven with advanced technology and DNA testing. The question is, what is the status of children born from such clandestine marriages, and how does the Religious Court respond to this decision? This research aims to interpret the Constitutional Court's Decision on the validity of a child's status as biological lineage to the person who caused their birth, as long as it can be proven with advanced technology and/or DNA testing. This research is a normative juridical study with a legal approach and case based on the Constitutional Court Decision regarding the status of children from clandestine marriages using the theory of fath al-dzari'ah. The research findings indicate that the Religious Court cannot reject trial requests regarding the status of children resulting from clandestine marriages, as long as it can be proven through advanced technology and/or attached DNA testing, even though the marriage status is considered invalid according to the State, as long as it is proven that the marriage is considered valid according to religion with evidence of a guardian and witnesses in the marriage.